Client satisfaction at the Midcentral Health and Massey University concussion clinic : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Psychology at Massey University - Leach, Roxanne Marie (Massey University, 2003)
The present study intended to evaluate the quality of the service provided by the Midcentral Health and Massey University Concussion Clinic. In doing so, the study first considered the nature of Mild Traumatic Brain Injury and concussion injury and rehabilitation and investigated different methods of measuring quality and weighed up the pros and cons of each method to chose the most appropriate method for this setting. As a result, the present study surveyed service satisfaction at the Concussion Clinic. A standardised measure (the Service Satisfaction Survey – 30) was chosen to counter previous methodological problems common to other studies of satisfaction. The main objective of this study was to provide feedback to the Concussion Clinic regarding satisfaction with aspects of their services and to simultaneously investigate relationships with satisfaction. On a whole, participants were generally satisfied with the Concussion Clinic service; conversely some aspects of the service that could be improved were identified. However caution has to be taken in analysing the results especially when inferring results to the whole population, due to this low response rate (twenty of the seventy-nine clients surveyed returned the survey). The second objective of the study was to evaluate the use of this method of evaluation, and the measure chosen, with this type of service. The measure chosen (the Service Satisfaction Scale –30) proved inappropriate for this service setting due to the length and irrelevant questions. Moreover the use of client satisfaction as a method to evaluate this service, even though it provided some data on satisfaction with services, also may not be justified for the reason that the clients were generally only seen once and the nature of outcome in this setting was unclear. This study demonstrated the need for more research in the area of service satisfaction in the health arena, in particular this type of setting; suggestions for this research are included in this study.
Keywords: Midcentral Health, Palmerston North; Brain injuries; Patient services; Concussion; Patient rehabilitation